Strategy for the Implementation of Information Technology and Social Media to Increase Value Added to Public Welfare Based on the Tourism Model in East Java - Dyah Sawitri; Andri Wijaya; Tri Cicik Wijayanti (Budapest International Research and Critics University, 2022)
The tourism model is a life entity that has great potential in the welfare of its people's lives towards an independent society. The tourism model can be directed to encourage initiatives to utilize the potential of the region through various development sectors. The tourism model is no longer only aimed at encouraging the growth of the number of visits but the quality of visits towards sustainable tourism development. In addition, the tourism model is also expected to become an economic locomotive to strengthen the value chain and tourism business ecosystem based on community strength. The tourism model is expected to become a local force that becomes a magnet for tourist arrivals, so that it can trigger inclusive economic activity. One of the famous tourist attractions and many objects is in Batu City, East Java. This research is a quantitative research using the type of explanatory research which aims to determine the effect of human resources, services on the improvement of tourist villages through social media. The sample used is 60 people as business actors in the tourist village of Bumiaji Village, Bumiaji District, Batu City. Statistical analysis used is Path Analysis approach. Based on the results of the analysis, it is known that there is a significant influence of human resources and services on social media in the Tourist Village of Bumiaji Village, Batu City. In addition, there is a significant influence of human resources, services and social media on increasing the tourism village of Bumiaji Village, Batu City. For this reason, a strategy for implementing advances in information and communication technology and the existence of social media is needed so that the tourism model designed is able to also build collaboration between institutions and the community, making the community more creative, innovative, and independent.